The Impact of CLILL Approach to Enhancing University Students’ Speaking and Creative Thinking Skills - Muhammad Guntur; Ririn Martuti; Hasmawaty Hasmawaty; Duwi Purwati; Hengki Wijaya; Zulfah Zulfah (STAI Hubbulwathan Duri, 2023)
In addition to being proficient in verbal communication, students must also acquire 21st-century competencies, which encompass creative thinking abilities. Content and Integrated Language Learning (CLIL) is a communication methodology that can be employed to concurrently enhance students' language proficiency and foster their creative cognition. This study investigates the influence of the Content and Language Integrated Learning (CLIL) strategy on the speaking and creative thinking abilities of students at IAIN Palopo, located in South Sulawesi, Indonesia. This study employed a quantitative methodology with a quasi-experimental design, encompassing 51 first-semester students enrolled in Indonesian language classes. The collection of data involved the utilisation of speaking tests, speaking assessment rubrics, and creative thinking skills examinations. Following data collection, the researchers conducted quantitative analysis using SPSS 25.00. They employed the one-way MANOVA and one-way MANCOVA tests for this purpose. The results showed that the CLIL approach had a significant effect on improving student's speaking skills and creative thinking skills. These results indicate that the CLIL approach can be used as a choice for teachers to develop students' speaking and creative thinking skills.